Development of world oil refining in the context of the coronavirus pandemic - A. P. Solomonov (Вестник университета)
The article is devoted to the generalisation and analysis of key trends in the global oil refining industry development in the current conditions of the coronavirus pandemic, when significant structural and organisational changes are taking place both in the world energy markets and in the states economies as a whole. In the context of the current situation, the largest oil refineries strategies are changing, taking into account the current lockdown risks. The article shows that the large oil reserves accumulation is one of the most significant challenges for the petroleum products global production, but the main risk is still a decrease in global demand for motor fuels. The author thinks that forecasts for the world oil refining development should be done carefully, taking into account the various trajectories of the post-pandemic world markets development, the gradual removal of  restrictions on transport links between countries, changes in the some sectors structure, in particular, international tourism. As part of our study, further options for the global value chains development in the industry have been assessed, which will tend to localise, and the “digital” factor in their development will be decisive.